2013
DOI: 10.1063/1.4806801
|View full text |Cite
|
Sign up to set email alerts
|

High-intensity coherent vacuum ultraviolet source using unfocussed commercial dye lasers

Abstract: Using two or three commercial pulsed nanosecond dye lasers pumped by a single 30 Hz Nd:YAG laser, generation of 0.10 mJ pulses at 125 nm (6 × 10(13) photons∕pulse) has been demonstrated by resonance enhanced four-wave mixing of collimated (unfocussed) laser beams in mercury (Hg) vapor. Phase matching at various vacuum ultraviolet (VUV) wavelengths is achieved by tuning one laser in the vicinity of the 6 (1)S0 → 6 (3)P1 resonance near 253.1 nm. A number of different mixing schemes are characterized. Our observa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 35 publications
1
24
0
Order By: Relevance
“…Near 11 eV, we measured a factor of two greater usable photon intensity (5 × 10 11 photons/pulse). 9 At 104 nm (12 eV), our usable VUV intensity of 9 × 10 10 photons/pulse, is similar to a previous estimate of ∼10 11 photons/pulse using a much more complex laser system. 24 At 89.6 nm (13.8 eV), we generated an order of magnitude more VUV than previously measured using Hg as a nonlinear mixing medium at that wavelength.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…Near 11 eV, we measured a factor of two greater usable photon intensity (5 × 10 11 photons/pulse). 9 At 104 nm (12 eV), our usable VUV intensity of 9 × 10 10 photons/pulse, is similar to a previous estimate of ∼10 11 photons/pulse using a much more complex laser system. 24 At 89.6 nm (13.8 eV), we generated an order of magnitude more VUV than previously measured using Hg as a nonlinear mixing medium at that wavelength.…”
Section: Discussionsupporting
confidence: 86%
“…This is about an order of magnitude smaller than we produce using collimated lasers in a 1 m long Hg cell. 11 Chénais et al reported the dependence of the "enhancement ratio," defined as the ratio of the VUV intensity with the vaporization laser on relative to that with the vaporization laser off, as a function of UV, visible, and ablation laser beam pulse energies. 29 We have carried out similar experiments but instead report the relative intensity of the VUV generated as functions of the three input laser pulse energies, shown in Fig.…”
Section: 9 Ev (125 Nm)mentioning
confidence: 99%
See 3 more Smart Citations